Estimation of Serum Copper and Magnesium Levels in Diabetic Nephropathy Patients - Khan, Farah Aziz; Khan, Mohd. Fareed; Patil, S.K.B.; Al-Jameil, Noura (Asian Journal of Biological and Life Sciences, 2013)
Diabetic Nephropathy is one of the well known complications of diabetes mellitus (DM). It has been reported in several studies that the metabolism of trace elements like copper (Cu) and magnesium (Mg) has altered in diabetes. Aim of the present study is to investigate serum Cu and Mg levels in diabetic nephropathy patients. The study includes 45 diabetic nephropathy patients and 40 controls. Fasting blood sugar (FBS), post parandial blood sugar (PBS) was determined by Glucose oxidase- Peroxidase (GOD POD) method, urinary albumin was estimated by immunoturbidometery and Cu, Mg was done by diethyldithiocarbamate and calmagite method respectively.Mean±SD values of FBS (162.8±21.9 mg/dl), PPBS (267.7±41.6 mg/dl), microalbumin (29.4±5.16 mg/L) and Cu (278.1±25.4 mg/dl) were found high in diabetic nephropathy patients with statistically significant difference (P<0.001) when compared with controls. Low MG levels (1.0 ± 0.17µg/dl) were observed in diabetic nephropathy patients than controls (1.97 ± 0.21µg/dl). A positive correlation was observed between serum Cu and FBS, PPBS and microalbumin of patients. While Mg shows negative correlation with FBS, PPBS and microalbumin. Progression of microalbuminuria is associated with poor glycemic control. Continued high levels of serum Cu and low serum levels of Mg lead to more distressing clinical complications, including retinopathy, hypertension and microvascular disease. Evaluation of serum Cu and Mg should be included in routine testing.